“One-stop” combined percutaneous left atrial appendage and atrial septal defect closure in atrial fibrillation: safety and feasibility from a single-center cohort - Wang, Gaofeng; Jie, Qiqiang; Xu, Kailing; Luo, Jie; Dong, Jing; Xie, Dujiang; Zhou, Ling (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPatients with atrial fibrillation (AF) and atrial septal defect (ASD) face elevated thromboembolic risks, yet evidence on combined left atrial appendage closure (LAAC) and ASD closure remains limited. We aimed to assess the feasibility and safety of a “one-stop” strategy for simultaneous LAAC and ASD closure.MethodsA retrospective analysis included 40 patients with non-valvular AF and ASD undergoing combined procedures (2016–2024). Procedural success, complications, and long-term outcomes (mean follow-up: 1,194.3 days) were analyzed.ResultsAll procedures were technically successful. No major complications (stroke, device embolization, or death) occurred during follow-up. Peri-device leak (PDL) was observed in 19 patients (47.5%), with only one case of device-related thrombus (resolved with anticoagulation).ConclusionThe “one-stop” approach is a safe and effective strategy for stroke prevention in AF patients with ASD, particularly those unsuitable for long-term anticoagulation.